Ozone exposure and health effects: a protocol for an umbrella review and effect-specific systematic maps - Joachim Heinrich; Dennis Nowak; Iana Markevych; Tianyu Zhao; Christian Janßen; Nadine Steckling-Muschack (BMJ Open)
Introduction Ambient ozone exposure may be adverse to health. Since the reported associations between ozone and health effects are heterogeneous and the underlying pathways are indistinct, the overall relationship remains unclear. Only a few overall syntheses of the evidence regarding ozone and health effects are available to date.Methods and analysis We plan to summarise the current evidence on ozone-related health effects systematically. First, to identify the possible associations between ambient ozone exposure and health outcomes, we will conduct an umbrella review. PubMed, Web of Science and grey literature will be searched for systematic reviews on exposure to ambient ozone and any possible health endpoints published before 31 May 2019. Data selection and extraction will be carried out by one reviewer, and a second reviewer will check the agreement of a sample of the studies. The methodological quality of the eligible systematic reviews and level of evidence regarding ozone and every specific health effect will be evaluated. Second, for each of the identified effects with a high level of evidence, comprehensive information retrievals will be conducted, considering both epidemiological and experimental studies. The study selection and data mapping will be carried out by one reviewer and checked by the second reviewer. We will summarise the information of the filtered epidemiological and experimental studies to conduct several systematic maps presenting the currently available evidence for the specific health effect. Because the association between ozone exposure and chronic obstructive pulmonary disease (COPD) is relatively well investigated, we will at least conduct one systematic map of ozone and COPD.Ethics and dissemination No ethical approval is required for this study. The completed umbrella review and systematic maps will be considered for publication and presentation. We will additionally upload the relevant data to publicly accessible online databases.PROSPERO registration number CRD42019123064.